Changes in diagnosis rates and behavioural traits of autism spectrum disorder over time. Issue 2 (October 2015) - Russell, Ginny; Collishaw, Stephan; Golding, Jean; Kelly, Susan E.; Ford, Tamsin
Abstract : Background: The increased proportion of UK children diagnosed with autism spectrum disorder (ASD) has been attributed to improved identification, rather than true increase in incidence. Aim: To explore whether the proportion of children with diagnosis of ASD and/or the proportion with associated behavioural traits had increased over a 10-year period. Method: A cross-cohort comparison using regression to compare prevalence of diagnosis and behavioural traits over time. Participants were children aged 7 years assessed in 1998/1999 ( n =8139) and 2007/2008 ( n =13831). Results: During 1998/1999, 1.09% (95% CI 0.86–1.37) of children were reported as having ASD diagnosis compared with 1.68% (95% CI 1.42–2.00) in 2007/2008: risk ratio (RR)=1.55 (95% CI 1.17–2.06), P=0.003. The proportion of children in the population with behavioural traits associated with ASD was also larger in the later cohort: RR=1.61 (95% CI 1.35–1.92), P<0.001. Increased odds of diagnosis at the later time point was partially accounted for by adjusting for the increased proportion of children with ASD-type traits. Conclusions: Increased ASD diagnosis may partially reflect increase in rates of behaviour associated with ASD and/or greater parent/teacher recognition of associated behaviours.